PENGARUH AKTIVITAS OLAH RAGA TERHADAP KADAR KOLESTEROL TOTAL DI POLI KLINIK JANTUNG - Angga Bhaim Ibrahim; Andika Herlina Marda Prawata (Stikes Syedza Saintika, 2020)
Cardiovascular disease generally is one of death causes each year. The was obtained from the medical records department of Dr. M. Djamil Padang showed that atherosclerotic disease was in first place of the 10 diseases biggest in onpatient department in 2014 (7038 people), Third position was congestive heart failure and hypertension was sevent position (4657). The research objective was to determine the relation of physical exercise with total cholesterol level Heart Poly Clinic.The type of research was Analytical. The population of this study were all patients with heart disease who visited the Heart Poly Clinic Dr. M. Djamil Hospital Padang (2385 people), the technic sampling of was accidental sampling method, the total sampling of 96 people. Was analyzed by using univariate and bivariate.The result of research found that 78.1% of respondents have high cholesterol levels, and 79.2% of respondents have moderate physical exercise. The bivariate analysis found that significant relation between the physical activity with total cholesterol levels in heart Polyclinic.In conclusion this study are expected to be used as inputs to the hospital on the relation of physical exercise levels of cholesterolemia and health workers to provide counseling to respondents during idle time while waiting queue for benefits of physical exercise in lowering the respondents cholesterol level.